Safety and efficacy of partial hepatectomy for huge (≥10 cm) hepatocellular carcinoma: A systematic review - Zhou, Yan-Ming (International Scientific Literature, Inc., 2011)
Huge (≥10 cm) hepatocellular carcinoma (HCC) is not uncommon at clinical presentation, and the surgical outcomes of such tumors are poor. This systematic review aimed to assess the safety and efficacy of partial hepatectomy for huge HCC. We performed a search on Medline and PubMed databases for all relevant studies published prior to December 2009. After exclusions, 21 studies remained for appraisal and data extraction. All studies were classified as level-4 evidence. The median overall perioperative morbidity and mortality rates were 29.2% (range: 13.6–72%) and 3.5% (range: 0–18.2%), respectively. The overall median survival since the partial hepatectomy was 20.7 months (range: 10.1–32 months), with median 1-, 3- and 5-year survival of 60.7% (range: 41–72.2%), 34% (range: 0–60.3%) and 28.6% (range: 0–54%), respectively. The median disease-free survival since the partial hepatectomy was 11.3 months (range: 5.5–32months), with median 1-, 3- and 5-year disease-free survival rates of 48.7% (range: 32–65.4%), 27.5% (range: 14.1–49%) and 20.7% (range: 9.5–43%), respectively. Partial hepatectomy can be performed safely and is associated with long-term survival in a subset of patients with huge HCC, but the evidence of benefit is currently weak.